COMPARISON OF SHORT VIDEO AND INFOGRAPHICS AS LEARNING MEDIA TO IMPROVE ENGLISH GRAMMAR DURING PANDEMIC - Khoirunnisa, Aulia; Sakhiyya, Zulfa (Journal of English Language and Literature Teaching, 2022)
This study aims to compare the effectiveness of using short video and infographics as learning media to improve student’s grammar knowledge in teaching present perfect tense. It also aims to analyze the improvement of teaching English ability during pandemics through the use of short videos and infographics at the 9th-grade student of SMP Negeri 25 Semarang. The research design is quasi-experimental research using two types of natural intact groups: experimental and control groups. The data were collected by observation using experimental, pre-test, and post-test techniques. Short videos are more effective than infographics in teaching the present perfect tense to 9th-grade students at SMP Negeri 25 Semarang, and for 9th-grade students at SMP Negeri 25 Semarang there is a significant contribution after teaching with short video and infographics on learning understanding the present perfect tense.